A Study on the MSMEs Growth of Empek-Empek Mama Raihan and Jajanan Bawah Pokok at Polbeng Business Expo Chapter II - Wianda Rahmalita; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This chapter talks about the results and how the Polbeng Business Expo Chapter II 2025 was carried out as a way to learn through experience and help small businesses grow. The event took place from May 20 to 22, 2025, at Politeknik Negeri Bengkalis, and was organized by students in the International Business Administration program. The activities included showing off businesses, holding creative contests, and running promotion events to bring together education, businesses, and the community. The main goal was to help small businesses like Empek-empek Mama Raihan and Jajanan Bawah Pokok. They got support with making their business profiles, using Instagram for online marketing, creating product catalogs, setting up the QRIS payment system, and making financial reports. The team promoted these businesses online for a whole month before the event, which helped raise awareness and get more people interested in visiting. The financial reports during and after the Expo showed that sales went up a lot compared to regular days. Overall, the Polbeng Business Expo Chapter II helped small businesses get more attention, improved their online marketing, made their financial management better, and gave students real-world experience in business advice and event planning. The success of the event shows that working together through exhibitions can really help small businesses grow and help build the local creative economy.